The tadpole of Hypsiboas guentheri (Boulenger) (Anura: Hylidae) - Almeida-Silva, Diego; Neto, Antonio Mollo; Mendes, Humberto Fonseca; Verdade, Vanessa Kruth (Zootaxa, 2016)
Hypsiboas guentheri is a species of treefrog that inhabits the surrounding vegetation of temporary and permanent ponds at the coastal region of Southern Brazil, in the States of Santa Catarina and Rio Grande do Sul (Langone 1997; Frost 2016). It belongs to the H. pulchellus species group (Faivovich et al. 2004, Duellman et al. 2016), this group contains 39 species (Frost 2016), but formal descriptions of tadpoles are missing for 15 of them (Kolenc et al. 2008; Pinheiro et al., 2016). Herein we describe tadpoles of H. guentheri collected in February 2014 in the accumulated water on an underpass for wildlife crossing at the RS-486 highway (29º30'44.8" S 50º06'29.9" W), Itati municipality, Rio Grande do Sul State, Brazil.